Post-segregational Killing and Phage Inhibition Are Not Mediated by Cell Death Through Toxin/Antitoxin Systems - Song, Sooyeon; Wood, Thomas K. (Frontiers in Microbiology, 2018)
The toxin/antitoxin (TA) field, born of controversy, is plagued by several prevailing misperceptions. For example, some TA systems stabilize plasmids and other genomic regions; however, the evidence of post-segregational killing by toxins of TA systems is weak. In addition, there are few credible reports of cell death via TA systems like MazF/MazE and via phage exclusion systems. Although many aspects of the biological roles of TA systems remain enigmatic, there are now some clear, confirmed TA functions: (i) phage inhibition, (ii) plasmid maintenance, (iii) stress response (including regulation of loci distinct from the TA pair itself), (iv) biofilm formation, and (v) persistence. Therefore, this opinion piece aims to challenge the oft-repeated claims of cell killing related to TA systems with the goal of emphasizing their primary biological role: constraining metabolism in a reversible manner. Hence, their roles in their five confirmed functions all stem from their ability to rapidly and reversibly reduce metabolic activity.